A Primer on Criminal Child Abuse and Neglect Law. (16th September 2013) - Abrams, Douglas E.
Abstract: This article surveys major aspects of criminal child abuse and neglect law encountered by judges, prosecutors and defense lawyers, child advocates, and child care professionals. The author, whose casebook, Children and the Law: Doctrine, Policy and Practice (West 4th ed. 2010) (with Sarah H. Ramsey), is required reading in law schools throughout the United States, analyzes both constitutional and statutory law.